VD_FINDINFO Arrêt / 2015 / 962 vom 7. Dezember 2015 - VD Tribunal cantonal (2015)
AA, RENTE D'INVALIDITÉ, RÉVISIONPRESTATION D'ASSURANCE, COMPARAISON DES REVENUS, REVENU D'INVALIDE, RESTITUTIONEN GÉNÉRAL | 18 LAA, 16 LPGA, 17 LPGA, 25 LPGA, 31 LPGA, 7 LPGA, 8 LPGA